Reconceptualization of English Teacher Beliefs and Practices Related to Teaching and Learning as a Result of Working at Nazarbayev Intellectual Schools - Akizhanova, Zhanar (Nazarbayev University Graduate School of Education, 2017)
The problem of teacher change in beliefs and practices is crucial in the light of recent educational reforms in Kazakhstan where Nazarbayev Intellectual schools are seen as an experimental site for development and implementation of the new learner-centered curriculum. The study focuses on the process of teacher change, in particular how purposefully selected four English teachers in one NIS schools have changed their beliefs and practices about teaching and learning as a result of working in the NIS environment. The case study, which employed an in-depth interview-based qualitative approach, also explores the main enabling and inhibiting factors that influenced the NIS teacher change process. The study also attempts to describe the model of teacher change process for those four NIS teachers. The study offers some key recommendations for different groups of stakeholders.
Keywords: educational reforms; NIS; learner-centered curriculum; teacher professional development; teacher learning; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education